Enhancing Professional Readiness Through Learner-Centered English for Specific Purposes in Business English Learning - Moelier, Dahlia Dahlima; Asyrafunnisa, Asyrafunnisa; Abeng, Andi Tenri (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to analyze the implementation of English for Specific Purposes (ESP) in English for Business learning for English Literature students at Bosowa University, focusing on instructional planning, learning strategies, and students’ perceptions of professional readiness. A qualitative case study approach was employed involving [X] lecturers and [Y] students who were purposively selected due to their direct engagement in the learning process. Data were collected through in-depth interviews, non-participant classroom observations, and document analysis, and analyzed using the Miles, Huberman, and Saldaña interactive model complemented by thematic analysis. Trustworthiness and research ethics principles ensured data validity. The findings indicate that ESP implementation was effective and systematic, as reflected in the alignment between needs analysis, authentic business-oriented materials, contextual learning activities, and observable improvements in students’ linguistic competence, learning engagement, self-confidence, and perceived professional readiness. The integration of learner-centered ESP principles, experiential learning, social constructivist interaction, and motivational support contributed to meaningful professional language development. Although challenges persist in mastering business terminology and formal discourse structures, the study highlights the importance of adaptive and reflective ESP design that responds to learner needs and workplace communication demands.